Value for Money in Ukraine’s HIV Response : Strategic Investment and Improved Efficiency - World Bank (World Bank, Washington, DC, 2016)
Ukraine experiences one of the most severe HIV epidemics in Europe. An HIV allocative efficiency analysis has been carried out, which revealed that there are several key opportunities to change the course of Ukraine’s HIV epidemic:Ukraine’s current HIV response already makes strategic use of available resources (around US$80 million in 2013) prioritizing Antiretroviral Therapy (ART) and prevention programs for people who inject drugs (PWID), men who have sex with men (MSM) and female sex workers (FSW). This investment, which successfully stabilized the epidemic – although at a high level – is unlikely to lead to further declines in new infections and deaths. The number of people on ART could be doubled to 130,000 (around 60 percent of all PLHIV) within the stipulated annual budget. At the time of completion of this study (mid 2015), only around 30 percent of Ukraine’s estimated 223,000 PLHIV received treatment against a global target of 81 percent by 2020. There is need to implement efficient and effective ART scale-up, achieve the national target of 118,240 PLHIV on ART by 2018, and plan for further increasing coverage to reach global targets - with a strong focus on HIV diagnosis among key populations.Continued funding for prevention programs for key populations remains critical beyond 2018.There is need for enhanced integration of HIV services with services for Tuberculosis, drug use treatment including Opioid Substitution Therapy, blood-borne viruses and sexual health.Ukraine’s HIV response requires a shared long-term vision on sustainable HIV financing and needs to harness the wider health sector reforms and emerging financing models. This policy brief is a result of a team effort involving the State Institution Ukrainian Center for Socially Dangerous Disease Control of the MOH of Ukraine and international partners. The study was part of the regional initiatives on HIV allocative efficiency analysis and funded and technically supported by the World Bank and UNAIDS. We greatly acknowledge the contributions of all the team members, stakeholders and other partners. There are major opportunities, but also major risks in relation to HIV investment decisions in Ukraine in the coming five years. While decreasing funding would lead to a marked increase in deaths, new infections and future health care costs, a smart approach to increasing HIV investment, could avert around half of the new infections and deaths up to 2030 compared to business as usual.